The Exact Estimation of the Hermite-Fejér Interpolation (Journal of Computational Mathematics, 2018)
The exact pointwise estimation of the Hermite-Fejér interpolation process based on the zeros of the Jacobi polynomial $P^{(α,β)}_n(x)(-1 ‹α,β ≤ 0)$ is given. The method employed is useful for other extended H-F interpolations also.